2022
DOI: 10.21203/rs.3.rs-2314578/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prevention of myopia shift and myopia onset using 0.01% atropine in premyopic children - A Prospective, Randomized, Double-masked, Crossover Trial

Abstract: To evaluate the efficacy of 0.01% atropine eye drops in preventing myopia shift and myopia onset in premyopic children. A prospective, randomized, double-masked, placebo-controlled, crossover trial was conducted over 13 months. Sixty premyopic children aged 6–12 years with cycloplegic spherical equivalent refraction (SER) > -0.75 D and ≤ + 0.50 D in both eyes were assigned in a 1:1 ratio to receive one drop of 0.01% atropine or placebo once nightly for 6 months (period 1), followed by a 1-month recovery per… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…The 650-nm LLRL may be a preventive measure for myopia. Previously, few studies [47][48][49] on myopia prevention were conducted because of ethical debates. Two recent studies 47,48 explored the possibility of using atropine for myopia prevention and reported opposite findings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 650-nm LLRL may be a preventive measure for myopia. Previously, few studies [47][48][49] on myopia prevention were conducted because of ethical debates. Two recent studies 47,48 explored the possibility of using atropine for myopia prevention and reported opposite findings.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, few studies [47][48][49] on myopia prevention were conducted because of ethical debates. Two recent studies 47,48 explored the possibility of using atropine for myopia prevention and reported opposite findings. For 650-nm LLRL, a clinical trial reported a 54.1% reduction in incident myopia among children with premyopia within 12 months.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in another recently published systematic review the estimated mean difference (MD) for myopia progression for atropine was found to be 0.29 D (95% CI 0.22-0.36; p = 0.03) [58]. In the present review, the most recent 16 out of initial 41 articles on RCTs were analyzed (Supplementary Table 3): a noticeable difference between these studies can be observed in terms of sample size [107][108][109], study length and design [110][111][112][113][114], the age of the children studied [106,109], location of trial [115][116][117], and the different atropine doses, which varied between 0.0025% and 1%, as well as the application frequency of drops [110,114,118,119], and lastly their aims [109,111,112,120]. Almost half of the selected studies were conducted in East Asia, in predominately Chinese ethnic children [109,110,114,115,[118][119][120].…”
Section: Atropinementioning
confidence: 99%
“…In the present review, the most recent 16 out of initial 41 articles on RCTs were analyzed (Supplementary Table 3): a noticeable difference between these studies can be observed in terms of sample size [107][108][109], study length and design [110][111][112][113][114], the age of the children studied [106,109], location of trial [115][116][117], and the different atropine doses, which varied between 0.0025% and 1%, as well as the application frequency of drops [110,114,118,119], and lastly their aims [109,111,112,120]. Almost half of the selected studies were conducted in East Asia, in predominately Chinese ethnic children [109,110,114,115,[118][119][120]. Four studies were conducted in Europe [107,111,112,116], two in India [113,117], one in Iran [108], one in the USA [121], and one in Australia [106].…”
Section: Atropinementioning
confidence: 99%
“…Three studies have indicated that nightly administration of low-concentration atropine eyedrops can delay the onset of myopia and/or reduce the shift of refractive error in the myopic direction. [14][15][16] The Low-Concentration Atropine for Myopia Prevention (LAMP2) study 17 reported in this issue of JAMA is the first large-scale, 2-year randomized clinical trial to investigate the effects of nightly administration of 0.05% or 0.01% atropine eyedrops vs placebo eyedrops in children without myopia. The objective of the study was to determine whether low-concentration atropine eyedrops could delay the onset of myopia and reduce the percentage of children who experience a 1.00 D myopic shift in refractive error.…”
mentioning
confidence: 99%